Contemporary views on the future of physiology—a report from the 2019 P-MIG focus group - Rodrigues, Luis Monteiro; Gregório, João; Wehrwein, Erica (Frontiers in Physiology, 2023)
Physiologists are seen as professionals with a unique understanding of life, health, and disease, essential to the progression of knowledge regarding human functions and health. Among these experts however, the thematic of the “Future of Physiology” has been regularly present in the agenda of physiology organizations around the world as various uncertainties about teaching and research in human physiology emerged. The Physiology Majors Interest Group (P-MIG) 2019 meeting provided the occasion for some strategic reasoning and planning, aiming to identify the trends that might drive future changes in human physiology. Twelve physiologists, all experts in different areas of Physiology research and teaching, nearly all based in North America, volunteered to participate in this focus group. The session was audio recorded. A verbatim transcript of the recording was then analyzed through thematic analysis, aiming to identify the most relevant themes for the future of Physiology and how these themes might unfold. The group concluded that a shared consciousness on general goals is present, meaning to preserve and develop the interdisciplinary/integrative nature, to promote more innovative teaching/learning practices, and to acknowledge technology as the main catalyst for research and teaching innovation and progress. This consciousness was present in all participants. The group also concluded that transformation will likely need to be more effective, and should involve the Physiological Societies and organizations around the world. Special emphasis was placed on the need to share common competences for curriculum definition, common guidance for teaching practice, and common assessment procedures, with particular attention recommended toward science communication.